2013
DOI: 10.4236/ss.2013.410084
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Course of the Inferior Gluteal Nerve and Artery: A Case Report and Literature Review

Abstract: Variations in the course of the inferior gluteal nerve and artery were observed in Japanese cases (4/94 sides). In these variation cases, the inferior gluteal nerve exited the pelvis from the upper edge of the piriformis (suprapiriformis foramen) in 4/4 sides (4.26%). In 2/4 sides (2.13%), the normal inferior gluteal artery was not observed, except that a fine artery exited the pelvis from the inferior piriformis foramen to form an "arch" with the superior gluteal artery under the gluteal maximus in 1/4 side. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Studies describing the relationship of the IGN to the PM, however, suggest that atypical variants are both less common and under-reported. One review showed that the IGN traverses superior to the PM in 0.1-4.4% of individuals [ 6 ]. The present case, like others, describes an instance where the nerve pierces the PM directly [ 7 , 8 ]; another case describes its complete absence [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies describing the relationship of the IGN to the PM, however, suggest that atypical variants are both less common and under-reported. One review showed that the IGN traverses superior to the PM in 0.1-4.4% of individuals [ 6 ]. The present case, like others, describes an instance where the nerve pierces the PM directly [ 7 , 8 ]; another case describes its complete absence [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Variants of the proximal IGN, particularly in relation to the PM, have not been thoroughly described. In the extant literature, few studies have reported variants ranging from total absence of the nerve [ 5 ] to it following atypical courses either above [ 6 ] or through [ 7 , 8 ] the muscle. Herein, we describe an unusual cadaveric case illustrating an atypical origin of the IGN.…”
Section: Introductionmentioning
confidence: 99%
“…9 The inferior gluteal nerve normally arises inferior to the piriformis and generally ends by supplying the gluteus maximus muscle and has no cutaneous branches; 1 however, this nerve may also show variations. 10,11 Authors in the past have reported a case of high division of the sciatic nerve with an anomalous double root of the inferior gluteal nerve emerging along both the upper and lower borders of the piriformis muscle to form the inferior gluteal nerve to supply the gluteus maximus muscle. 10 Yan et al also…”
Section: Figure Showing High Division Of the Sciatic Nerve Into The Tmentioning
confidence: 99%
“…11 Bhattacharya et al reported multiple variations in the left gluteal region where they noted double piriformis, high division of the sciatic nerve, and dual nerve supply of the gluteus maximus. The additional supply to the gluteus maximus was derived from the common peroneal nerve.…”
Section: Figure Showing High Division Of the Sciatic Nerve Into The Tmentioning
confidence: 99%
“…However, Jun Yan et al [16] reported inferior gluteal nerve exiting the pelvis from the upper border of the piriformis in 4 of 94 gluteal regions (4.26%).…”
Section: Shylaja D K B R Ramesh Study Of Anatomi-cal Variations Of mentioning
confidence: 99%